Role of Fine-needle Aspiration and Survival Analysis of Chondrosarcomas - Pravinkumar Vijaykumar Ghongade; Bharat Umakant Patil; Anupama Gupta; Nitin M. Gangane (Wolters Kluwer Medknow Publications, 2024)
Background: Chondrosarcomas (CSs) are the second-most common primary malignant tumor of the bone and are a malignant tumor of cartilaginous origin. Aim: The aim of the study was to analyze the accuracy of fine-needle aspiration cytology (FNAC) in diagnosing CS and its correlation with histologic diagnosis and evaluate the survival outcome and prognostic factors in CS. Setting and Design: Retrospective study conducted from January 2013 to December 2019. Materials and Methods: Data regarding clinical findings, FNAC diagnosis, histopathological, radiological findings, and patient status were retrieved. Statistical Analysis: Kaplan-Meier curve and Log Rank (Montel Cox) analysis were used for statistical analysis. Results: Twenty-six cases of CS were selected. The accuracy of diagnosing CS on FNAC was 61.53%, and the accuracy in interpreting it as a malignant lesion was 92.30. Overall survival outcome in CS patients was 92.23% at 1 year, 73.23% at 3 years, and 61.32% at 5 years. Survival outcomes significantly altered depending on the histological variants, metastases status, and histological grading, which showed Chi-square values of 31.77 (P ≤ 0.001), 8.43 (P = 0.011), and 6.33 (P = 0.043), respectively. The median survival time of CS was 2214.98 days, with a standard error of 362.83. Patient age, gender, tumor size, and skeletal versus extraskeletal CS had little impact on CS survival (Chi-square value = 0.464 (P = 0.496 NS), 0.570 (P = 0.450 NS), 2.83 (P = 0.242 NS), 0.125 (P = 0.724 NS), respectively. Conclusion: FNAC is a beneficial, reliable tool for screening and diagnosing CS. Prognostic factors such as histological variants, histological Grade 1 and 2, and no metastases status are associated with good survival. Patient age, tumor size, and extraskeletal location are not associated with prognosis and survival.